Oral magnesium supplements for cancer treatment‐induced hypomagnesemia: Results from a pilot randomized trial. Issue 4 (14th December 2021) - Awan, Arif; Basulaiman, Bassam; Stober, Carol; Clemons, Mark; Fergusson, Dean; Hilton, John; Al Ghareeb, Waleed; Goodwin, Rachel; Ibrahim, Mohammed; Hutton, Brian; Vandermeer, Lisa; Mallick, Ranjeeta; et al.
Abstract: Background and Aims: Optimal management of cancer treatment‐induced hypomagnesemia (hMg) is not known. We assessed the feasibility of using a novel pragmatic clinical trials model to compare two commonly used oral Mg replacement strategies. Methods: Patients with grade 1 to 3 hMg while receiving either platinum‐based chemotherapy or epidermal growth factor receptor inhibitors (EGFRI) were randomized to oral magnesium oxide (MgOx) or oral magnesium citrate (MgCit). The trial methodology utilized the integrated consent model. Feasibility would be successful if; accrual rate was ≥5 patients a month and if measures of patient and physician engagement, were > 50%. Secondary endpoints included; comparison of Mg levels, cardiac arrhythmias, and rates of treatment delay/hospitalizations. Results: From July 2016 to December 2017, an average of 1 patient a month was accrued. All 15 eligible and approached patients consented to participate in the study (100% engagement) and 7/15 were randomized to MgOx and 8/15 to MgCit. The percentage of physicians who approached patients for the study was 4 of 6 (66.6% engagement). The mean slope of change in Mg (mmol/L/day) was 0.0022 (95% CI: −0.0001 to 0.0044) for MgOx and 0.0006 (95% CI, −0.0012 to 0.0024) for MgCit ( P = .2123). Three patients (20%) required IV magnesium while on the study (2 MgCit and 1 MgOx). Grade 1 diarrhea occurred in 3 patients in the MgCit arm. Conclusion: Despite oral magnesium tolerability and meeting most of its feasibility endpoints, this study did not meet its target accrual rate. Alternative designs would be necessary for a definitive efficacy study.